INTERAKTIV OQÍTÍW METODLARÍ TIYKARÍNDA OQÍWShÍLARDÍŃ KREATIVLIK KOMPETENCIYALARÍN QÁLIPLESTIRIW - Saparbaeva, Tazagul Tlekovna (SCIENCE and SOCIETY, 2026)
The article analyzes the development of students’ creative thinking in the context of the rapid digitalization of the education system. The role of digital pedagogical technologies and interactive teaching methods in improving the effectiveness of the educational process is highlighted. The pedagogical and psychological aspects of creativity, the stages of creative thinking development, and the importance of innovative teaching methods in modern education are also examined. The study analyzes scientific approaches to the theory of pedagogical technologies and substantiates the effectiveness of interactive methods in developing students’ independent thinking, problem-solving abilities, and the generation of new ideas. The results show that the digital educational environment plays an important role in developing students’ intellectual and creative potential.